The Effect of Transfer Pricing and Profitability on Tax Avoidance Empirical Study in Industrial Sector Companies - Adiguna, Septian; Ritonga, Ferdiansyah (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
This study aims to evaluate the influence of transfer pricing and profitability on tax avoidance in industrial sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2023. The analytical methods employed include descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, t-tests, and the determination coefficient test using SPSS software with a 5% significance level. The sample used in this study consists of 139 observations. The results indicate that transfer pricing has a significant effect on tax avoidance, while profitability does not have a significant impact on tax avoidance. These findings suggest that companies tend to use transfer pricing strategies to minimize tax burdens and increase after-tax profits. Conversely, changes in profitability levels cannot be considered a reliable indicator to predict changes in corporate tax avoidance behavior. Thus, this study highlights the importance of transfer pricing as a key factor in corporate tax avoidance strategies, while profitability does not show a significant relationship with tax avoidance. These findings contribute to the literature on tax avoidance and can serve as a reference for policymakers in understanding the dynamics of tax avoidance in the industrial sector.